Effect of Working Table and Bandsaw Speed on the VZ 400-SA Machine in Obtaining the Optimal Width of Steel Plate - Wajdi, Farid; Rahman, Fandi Nur; Supriyadi, Supriyadi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The size of the material test specimen determines the accuracy of the material characteristics. This research was conducted to obtain the optimal tensile test specimen size by optimizing the cut parameters on the VZ-400 SA cutting machine. The material used is SNI 07-2054-2007 standard angled steel with a thickness of 5 mm. Optimization of machine parameters was carried out using the Taguchi method to measure the effect of work table speed (mm/s) and saw blade speed (m/min) on the response to the width of the rectangular cutting product. Cut width limit between 34-36 mm. Data was collected by conducting experiments 9 times with 3 replications. The results showed that the factor that most influenced the size of the width of the cut was the speed of the work table with a contribution of 86.49%, while the speed of the saw blade was 1.64% with an error of 11.87%. The optimal size of the test specimen is produced from the table speed parameter of 2 mm/s and the saw cutting speed of 90 m/min. Cutting validation was conducted in triplicate, and the result showed an average plate width of 34.7 mm with an error of 0.02.